Growth Giant Prawns (Macrobracium Rosenbergii) With Different Stock Densities On The Minapadi System: English - Mahendra, Mahendra; Farah Diana; Dini Islama; Citra Dina Febrina (International Journal of Science, Technology & Management, 2021)
Minapadi is a fish rearing system in rice fields that is carried out with rice plants. This study aims to increase the income of farmers with high productivity of rice yields and increase the production of giant prawns. The method used is a Completely Randomized Design (CRD) experiment with 3 treatments and 3 replications. The treatments were: P1 = stocking density of 100 birds/plot, P2 = stocking density of 200 birds/plot, P3 = stocking density of 300 birds/plot. This research was conducted for 90 days. Parameters observed were rice productivity and growth. The results showed that the best treatment was P2 = stocking density of 200 birds/plot. by producing an average value of rice productivity of 5 kg/50 m2 and an average value of growth of giant prawns of 4.72%.